Pulmonary Microbial Composition in Sepsis-Induced Acute Respiratory Distress Syndrome - Zhang, Peng; Liu, Baoyi; Zheng, Weihao; Chen, Yantang; Wu, Zhentao; Lu, Yuting; Ma, Jie; Lu, Wenjie; Zheng, Mingzhu; Wu, Wanting; Meng, Zijie; Wu, Jinhua; et al. (Frontiers in Molecular Biosciences, 2022)
Background: Acute respiratory distress syndrome (ARDS) is an unresolved challenge in the field of respiratory and critical care, and the changes in the lung microbiome during the development of ARDS and their clinical diagnostic value remain unclear. This study aimed to explore the role of the lung microbiome in disease progression in patients with sepsis-induced ARDS and potential therapeutic targets. Methods: Patients with ARDS were divided into two groups according to the initial site of infection: intrapulmonary infection (ARDSp, 111 cases) and extrapulmonary infection (ARDSexp, 45 cases), and a total of 28 patients with mild pulmonary infections were enrolled as the control group. In this study, we sequenced the DNA in the bronchoalveolar lavage fluid collected from patients using metagenomic next-generation sequencing (mNGS) to analyze the changes in the lung microbiome in patients with different infectious sites and prognoses, and before and after antibiotic treatment. Results: The Shannon Wiener index indicated a statistically significant reduction in microbial diversity in the ARDSp group compared to the ARDSexp and control groups. The ARDSp group was characterized by a reduction in microbiome diversity, mainly in the normal microbes of the lung, whereas the ARDSexp group was characterized by an increase in microbiome diversity, mainly in conditionally pathogenic bacteria and intestinal microbes. Further analysis showed that an increase in Bilophila is a potential risk factor for death in ARDSexp. An increase in Escherichia coli, Staphylococcus aureus, Candida albicans, enteric microbes, or conditional pathogens may be risk factors for death in ARDSp. In contrast, Hydrobacter may be a protective factor against ARDSp. Conclusions: Different initial sites of infection and prognoses are likely to affect the composition and diversity of the pulmonary microbiome in patients with septic ARDS. This study provides insights into disease development and exploration of potential therapeutic targets.